Investigating genetic damage in workers occupationally exposed to methotrexate using three genetic end-points - Deng, Hongping; Zhang, Meibian; He, Jiliang; Wu, Wei; Jin, Lifen; Zheng, Wei; Lou, Jianlin; Wang, Baohong (Mutagenesis, 2005)
Genetic damage in workers occupationally exposed to an antineoplastic drug was studied using the micronucleus (MN) test, the comet assay, the hprt gene mutation assay and the TCR gene mutation assay. The subjects were divided into two groups: (i) 21 workers from a plant producing methotrexate (MTX); (ii) 21 controls were matched according to age, gender and smoking. Fresh blood samples were collected from the workers and controls. The results of the MN test showed that the mean micronuclei rate (MNR) and mean micronucleated cell rate (MCR) in workers were 10.10 ± 0.95‰ and 8.05 ± 0.75‰, respectively, which were significantly higher than those (5.48 ± 0.82‰ and 4.38 ± 0.58‰) in controls (P < 0.01). It was found in the comet assay that the mean tail length (MTL) of workers and controls were 1.30 ± 0.06 µm and 0.07 ± 0.01 µm, respectively. There was a significant difference between workers and controls for MTL (P < 0.01), but the difference between the mean tail moment (MTM, 0.23 ± 0.03) of workers and MTM (0.17 ± 0.04) of controls was not significant (P > 0.05). The results of hprt gene mutation assay showed that the average mutation frequency (Mf-hprt) of hprt in workers was 1.00 ± 0.02‰, which was significantly higher than that (0.86 ± 0.01‰) in controls (P < 0.01). Meanwhile, the results of TCR gene mutation assay indicated that Mfs-TCR gene mutation frequencies of workers and controls were 6.87 ± 0.52 × 10−4 and 1.67 ± 0.14 × 10−4, respectively, which were significantly different (P < 0.01). The results of our experiment suggest that genetic damage is detectable in the 21 workers occupationally exposed to methotrexate.